Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the equation step by step:
Given:
[tex]\[ \frac{1}{\sqrt[3]{2x - 3}} = 2 \][/tex]
Step 1: Get rid of the fraction by taking the reciprocal on both sides of the equation.
[tex]\[ \sqrt[3]{2x - 3} = \frac{1}{2} \][/tex]
Step 2: Cube both sides to remove the cube root.
[tex]\[ (\sqrt[3]{2x - 3})^3 = \left( \frac{1}{2} \right)^3 \][/tex]
[tex]\[ 2x - 3 = \frac{1}{8} \][/tex]
Step 3: Isolate [tex]\( x \)[/tex] by solving the resulting linear equation:
[tex]\[ 2x - 3 = \frac{1}{8} \][/tex]
Step 4: Add 3 to both sides to move the constant term to the right-hand side:
[tex]\[ 2x = \frac{1}{8} + 3 \][/tex]
Step 5: Convert 3 to a fraction with the same denominator as [tex]\(\frac{1}{8}\)[/tex]:
[tex]\[ 3 = \frac{24}{8} \][/tex]
[tex]\[ 2x = \frac{1}{8} + \frac{24}{8} \][/tex]
Step 6: Combine the fractions:
[tex]\[ 2x = \frac{25}{8} \][/tex]
Step 7: Divide both sides by 2 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{25}{8} \times \frac{1}{2} \][/tex]
[tex]\[ x = \frac{25}{16} \][/tex]
Step 8: Convert the fraction to a decimal for a more intuitive answer:
[tex]\[ x = 1.5625 \][/tex]
Thus, the solution to the equation [tex]\(\frac{1}{\sqrt[3]{2 x-3}}=2\)[/tex] is:
[tex]\[ x = 1.5625 \][/tex]
This completes the step-by-step solution of the given equation.
Given:
[tex]\[ \frac{1}{\sqrt[3]{2x - 3}} = 2 \][/tex]
Step 1: Get rid of the fraction by taking the reciprocal on both sides of the equation.
[tex]\[ \sqrt[3]{2x - 3} = \frac{1}{2} \][/tex]
Step 2: Cube both sides to remove the cube root.
[tex]\[ (\sqrt[3]{2x - 3})^3 = \left( \frac{1}{2} \right)^3 \][/tex]
[tex]\[ 2x - 3 = \frac{1}{8} \][/tex]
Step 3: Isolate [tex]\( x \)[/tex] by solving the resulting linear equation:
[tex]\[ 2x - 3 = \frac{1}{8} \][/tex]
Step 4: Add 3 to both sides to move the constant term to the right-hand side:
[tex]\[ 2x = \frac{1}{8} + 3 \][/tex]
Step 5: Convert 3 to a fraction with the same denominator as [tex]\(\frac{1}{8}\)[/tex]:
[tex]\[ 3 = \frac{24}{8} \][/tex]
[tex]\[ 2x = \frac{1}{8} + \frac{24}{8} \][/tex]
Step 6: Combine the fractions:
[tex]\[ 2x = \frac{25}{8} \][/tex]
Step 7: Divide both sides by 2 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{25}{8} \times \frac{1}{2} \][/tex]
[tex]\[ x = \frac{25}{16} \][/tex]
Step 8: Convert the fraction to a decimal for a more intuitive answer:
[tex]\[ x = 1.5625 \][/tex]
Thus, the solution to the equation [tex]\(\frac{1}{\sqrt[3]{2 x-3}}=2\)[/tex] is:
[tex]\[ x = 1.5625 \][/tex]
This completes the step-by-step solution of the given equation.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.